Assessment of Hydrochemical Characteristics and Water Quality as Monitoring of Environmental Conditions in Shallow Groundwater and Kinokawa River, Wakayama Prefecture, Japan - Endah Kinarya Palupi; Keodouangdy Yongthong; Afi Candra Trinugraha (CV FOUNDAE, 2024)
Shallow groundwater and river water problems in each country are caused by various factors such as natural factors such as natural disasters, human activity factors such as waste pollution, and others. In this study, we analysed the hydrochemical characteristics of river water to determine the water quality of shallow groundwater and Kinokawa river in Wakayama region of Japan. Shallow groundwater and river water samples were taken along the Kinokawa river at a total of 86 points. The water samples were analysed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). In this case, we investigated physicochemical parameters such as total dissolved solids which mainly depend on the concentration of major ions such as Ca, Mg, Na, K, Cl, Li, HCO3, NO3 and SO4 which are used to characterise river water quality. The results of this study show that the calculated values of SAR, PI, Na%, MH and RSC indicate good groundwater use for irrigation purposes. Comparison of geochemical data showed that more than 75% SAR, 94% PI, 80% %Na, and 97% MH indicated a good environmental condition category and the river water can be used for irrigation purposes. The water quality information presented in this paper will be useful for sustainable management of water resources in the study area.